Acceptability in Telemedicine Service: The Certainty of Human Wisdom - Karia, Noorliza (Technology Transfer and Entrepreneurship (Discontinued), 2015)
Background: Green business and smart growth have inspired healthcare providers promoting telemedicine. The investment in innovation of healthcare and health-related services is aimed to be a nation with healthy society through telemedicine (health service system) that is efficient, technologically appropriate, and environmentally adaptable and consumer friendly with prominence and eminence on quality, innovation and value of health. However little is known about factors influencing users’ to use telemedicine service. Objective: This article aims to understand human dimensions/factors of telemedicine service acceptance. It further investigates degree of human wisdom and its impact on acceptability. Method: Based on a survey of 89 participants, PLS-SEM is conducted to analyze survey data. Results: The findings identify and construct the degree of human wisdom certainty in knowledge, observation and proven of true. The results confirm that the human wisdom have a positive significant impact on user to use telemedicine service. The higher the level of certainty, the greater the user’s acceptability. Conclusion: This research contributes to the identification, conceptualization and measurement of human wisdom and acceptability. The degree of wisdom enhance the user’s confident in telemedicine service acceptance. It suggests the needs for healthcare providers to consider users’ participation into new and advanced telemedicine technologies when healthcare providers want to upgrade their technologies or telemedicine service.
Keywords: telemedicine service acceptance